Analisis Konsumsi Buah-buahan pada Tingkat Rumah Tangga di Daerah Istimewa Yogyakarta = Analysis Of From Consumption At The Household Level in Yogyakarta Special Territoty - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
The present was analysing what factors were responsible for consumption of individual fruit species of a household in rural and urban areas in Yogyakarta Special Territory, with income classified as low, intermediate, and high. SUSENAS data of 1999 of Yogyakarta Special Territory with total responden of 2240 household. Tobit analysis was adopted for estimation purposes to qualitatively differentiate limited observations and unlimited (continous) ones. The results showed that consumption of banana, papaya, rambutan of household was dominantly affected by income, price of the corresponding fruit species, and family size, while in urban area, it was dominantly affected by the price of the fruit, price of fruit substitute, and family size.